Ascending aorta diameters measured by echocardiography using both leading edge-to-leading edge and inner edge-to-inner edge conventions in healthy volunteers. (4th October 2013) - Muraru, Denisa; Maffessanti, Francesco; Kocabay, Gonenc; Peluso, Diletta; Bianco, Lucia Dal; Piasentini, Eleonora; Jose, Seena Padayattil; Iliceto, Sabino; Badano, Luigi P.
Abstract: Aims: Reference ranges of ascending aorta diameters (AAoD) for two-dimensional echocardiography (2DE) using inner edge (IE) convention are lacking, preventing the comparison of AAoD measurements by 2DE with those obtained by other imaging modalities. Methods and results: We used harmonic imaging 2DE to prospectively study 218 healthy volunteers (56% women, 42 ± 15 years, 18–80 years). Measurements were performed at the level of aortic root (AoR), sinotubular junction (STJ), and proximal tubular portion (TAo, 1 cm from the STJ) using both leading edge (LE) and IE conventions at end-diastole and end-systole. Feasibility of AAoD measurements between end-diastole and end-systole was similar at AoR and STJ levels, but it was significantly different at TAo level (82 vs. 96%, respectively, P < 0.0001). Ascending aorta diameters indexed to height were larger in men than in women ( P < 0.0001). After adjusting for the effect of gender, only age and body surface area (BSA) were independent predictors of AAoD at multivariable analysis. Average end-diastolic AoR, STJ, and TAo diameters measured using IE convention were similar between genders (17 ± 2, 15 ± 2, and 15 ± 2 mm/m 2, respectively). Corresponding AAoD measured using the LE convention were 18 ± 2, 16 ± 2, and 17 ± 4 mm/m 2, respectively. On average, the end-systolic AAoD measured using LE were 2 mm larger than those performed using IE or at end-diastole. Mean aortic wall thickness was 2.4 ± 0.8 mm. Conclusion: End-diastolic AAoD measured using IE were significantly smaller than those obtained either using LE convention or at end-systole. Gender-specific reference values for AAoD indexed for BSA should be used to identify ascending aorta pathology.